The Accuracy of Portable Ultrasound Bladder Scanner Measurements of Postvoid Residual Volume in Women With Pelvic Organ Prolapse. Issue 5 (September 2019) - Theisen, John Graham; Deveneau, Nicolette E.; Agrawal, Anu; Kinman, Casey; Gaskins, Jeremy; Meriwether, Kate; Francis, Sean L.
Abstract : Objectives: The purpose of this study was to evaluate the accuracy of portable bladder scanner postvoid residual (PVR) volume measurements in patients with pelvic organ prolapse. A secondary goal was to determine whether covariates such as bladder volume and stage of prolapse affect bladder scanner accuracy. Study Design: Complex urodynamic studies were performed on 70 patients with stage II or greater prolapse. Complex urodynamic studies included measurement of maximum bladder capacity (MBC) as well as measurement of PVR by urethral catheterization before, and following, complex filling cystometry. For each catheterized PVR, a corresponding bladder scanner measurement was obtained; the primary outcome was the difference between these measurements. In addition, bladder scanner measurements of MBC were compared with MBC by urodynamic pump. Measurements were compared by paired t test. Linear regression was used to assess association between covariates and bladder scanner error. Results: There was no significant difference between catheter and bladder scanner PVR at the initial (mean difference, 5.94 mL; 95% confidence interval [CI], −3.8 to 15.7) or final (mean difference, 1.37 mL; 95% CI, −10.9 to 13.6) measurements. Maximum bladder capacity measurements by bladder scanner were significantly smaller than catheterized measurements (mean difference, −21.3 mL; 95% CI, −40.3 to −2.3). Stage III/IV prolapse was associated with increased bladder scanner error ( P = 0.03). Conclusions: The portable bladder scanner accurately measures PVR in patients with pelvic organ prolapse and could be considered as an alternative to catheterized assessment. However, stage III/IV prolapse is associated with increased bladder scanner error, which should be considered when determining appropriate candidates for bladder scanner PVR assessment.